The Role of Generative AI in Enhancing Second Language Writing Fluency - Rusdiana Junaid; Affan Ramadhana; Nur Qalbi Rustan; Suci Putri Damayanti; Muh. Hardiansyah Pateha (Universitas Islam Negeri Palopo, 2024)
This mixed-methods quasi-experimental study evaluated the efficacy of generative AI-assisted feedback in improving EFL students' academic writing in comparison to traditional instructor feedback. Thirty-two sixth-semester students enrolled in an academic writing course were allocated to either an AI-assisted experimental group (n = 16) or a teacher-feedback control group (n = 16). Students submitted pre- and post-test argumentative essays assessed for fluency (total word count; average sentence length), correctness (errors per 100 words), and coherence (discourse markers; cohesion index). A questionnaire and semi-structured interviews elicited perceptions and ethical apprehensions. The AI group had superior advancements in fluency and coherence, although accuracy enhanced in both groups. Students appreciated immediacy and specificity, while acknowledged the dangers of excessive dependence and ambiguity in writing. Research indicates that AI can enhance instructor feedback by providing additional revision chances and fostering autonomy within integrity-centered advice in EFL academic writing.